2009
DOI: 10.1200/jco.2008.19.3797
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind 2 × 2 Trial of Low-Dose Tamoxifen and Fenretinide for Breast Cancer Prevention in High-Risk Premenopausal Women

Abstract: A B S T R A C T PurposeTamoxifen and fenretinide are active in reducing premenopausal breast cancer risk and work synergistically in preclinical models. The authors assessed their combination in a two-by-two biomarker trial. Patients and MethodsA total of 235 premenopausal women with pT1mic/pT1a breast cancer (n ϭ 21), or intraepithelial neoplasia (IEN, n ϭ 160), or 5-year Gail risk Ն 1.3% (n ϭ 54) were randomly allocated to either tamoxifen 5 mg/d, fenretinide 200 mg/d, their combination, or placebo. We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 36 publications
0
98
0
1
Order By: Relevance
“…Furthermore, our results are not inconsistent with a retrospective study of 130 African Americans and Latino breast cancer patients where plasma IGF1 levels were not associated with increased risk of breast cancer recurrence among postmenopausal women (Vadgama et al 1999), although a significant association was found among premenopausal women. In a recent trial that investigated the influence of tamoxifen on IGF1 among 235 premenopausal breast cancer women (Decensi et al 2009), tamoxifen Table 3 The sample size, median (IQR), mean (S.E.M. ), and hazard ratio (stratified by matched pairs) for IGF1 as a predictor of additional breast cancer events (recurrence or new primary) in WHEL among the full and postmenopausal samples…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results are not inconsistent with a retrospective study of 130 African Americans and Latino breast cancer patients where plasma IGF1 levels were not associated with increased risk of breast cancer recurrence among postmenopausal women (Vadgama et al 1999), although a significant association was found among premenopausal women. In a recent trial that investigated the influence of tamoxifen on IGF1 among 235 premenopausal breast cancer women (Decensi et al 2009), tamoxifen Table 3 The sample size, median (IQR), mean (S.E.M. ), and hazard ratio (stratified by matched pairs) for IGF1 as a predictor of additional breast cancer events (recurrence or new primary) in WHEL among the full and postmenopausal samples…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in UM or even EM, the tamoxifen dose may be personalized to a lower range, for example, 5-10 mg per day, because we showed that low-dose tamoxifen maintains antiproliferative activity on BC whereas toxicity may be reduced. [38][39][40] CYP2D6 genotyping could be evaluated together with serum endoxifen levels and biomarkers of tamoxifen activity and safety (for example, mammographic density, IGF-I, SHBG, lipids and endometrial thickness) after a short period of treatment. Such interaction may be a key point to personalized treatment and dose, in a manner that is similar to monitoring statin therapy with cholesterol levels and biphosphonates with bone density.…”
Section: Serrano Et Almentioning
confidence: 99%
“…An important characteristic of breast density is that it is reducible, [64][65][66][67][68][69] and preliminary studies have shown that breast density may serve as a biomarker for the effect of preventive interventions on breast cancer risk. 17 The first International Breast Cancer Intervention Study (IBIS) trial of Tamoxifen TM versus placebo showed that women in the Tamoxifen group who had a 10% or greater reduction in breast density demonstrated a 63% reduction in breast cancer risk but those who experienced less than 10% breast density reduction showed no risk reduction.…”
Section: Breast Composition and Radiographic Appearancesmentioning
confidence: 99%